The foreign policy of modern Japan (University of California Press, 1977)
The book comprises a broad-gauged exploration of the processes and institutions involved in the making of Japanese foreign policy. The essays also focus on major issues that have confronted Japan in the international arena during recent decades, as well as on those that are likely to be of central concern in the future.